Autosomal Recessive Non-Syndromic Hearing Loss: A Case Report with a Novel TRIOBP Gene Variant - Shweta Jangam; Manju Kurup; Preeti Arora; Shruti Jawale; Prashant Duraphe; Sanjay Gupte (Case Reports in Clinical Practice)
In the present case report, we have found a novel variant for TRIOBP in a patient with congenital hearing loss. The patient is an 8-year-old female with hearing loss, the first child of consanguineous parents. To identify the underlying genetic defect, whole genome sequencing was performed. Carrier screening of the parents was also conducted. The results showed a homozygous autosomal recessive missense c.5849C>T (p.Pro1950Leu) variant in exon 16 of the TRIOBP gene. To our knowledge, this variant has not been previously reported as either a pathogenic or a benign variant. The novel TRIOBP variant found in the present study broadens the range of TRIOBP mutations implicated in hearing loss. Accordingly, the results of this study may be important for genetic counseling.